Energy advice in Germany: a market actors' perspective. Issue 4 (5th November 2018) - Ringel, Marc
Abstract : Purpose: This study reviews present trends, barriers and outlooks for the future as seen by actors in the energy advice services market in Germany. As Germany is one of Europe's leading markets for energy services, this review aims to highlight energy sector management issues that exist throughout Europe. Design/methodology/approach: This study combines qualitative and quantitative research approaches, using seven qualitative stakeholder interviews and a semi-structured survey covering over 500 energy advisors. Based on the present market, this study seeks to identify barriers against further market development, regulatory measures that can promote market development and business models for energy services likely to emerge in the future. Findings: Significant barriers persist, despite a strong government commitment to support development of the energy services markets. The barriers encourage market actors to maintain the status quo rather than use innovate new service models. To support innovative business models, action is needed by both industry associations and the government to create a stronger demand pull for advice services. Originality/value: This paper provides a new sectoral overview of Europe's biggest energy service market as seen from a market actor perspective. It focuses on the analysis of barriers and business models to derive needs for further capacity building within the sector and for political governance to trigger further market dynamics.